Analysis of the Effect of Side Obstacles on Performance on the Z.A. Pagaralam Road Section - Romadona, Suci Fitria; Dewantoro, Fajar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Development in Bandar Lampung is increasing rapidly, causing an increase in transportation development. The development of transportation in the city of Bandar Lampung is currently still experiencing severe problems, so traffic hours often occur. The high level of congestion on the highway is caused by several things, including the unbalanced road capacity and vehicle volume and the presence of side obstacles, which add to congestion on the Z.A. Pagaralam road section. Apart from being a public road, Pagaralam is also located in one of the busiest economic centers in the city of Bandar Lampung. Along this stretch of road are campuses, schools, shops, pharmacies, shopping centers, and street vendors, and it is also a transfer point for passengers moving from one public transport to another, causing many side obstacles to occur on the road. To overcome this, it is necessary to analyze the influence of side obstacles on traffic performance. Data analysis was carried out using the PKJI 2014 method. The analysis of traffic volume obtained a value of 4747.75 cur/hour. The analysis results of the highest side obstacles were obtained on Tuesday at 12.00 – 14.00 segment 1 amounting to 838.90 incident weights. Keywords: Traffic Volume, Side Obstacles, PKJI 2014.